SAHEL REGION IN FRENCH POSTCOLONIAL DISCOURSE: MACRON'S PRODUCTION OF SPACE AND SECURITY RHETORIC - Putri, Azzahrah F. A; Wardani, Abellia Anggi, Dr. (UI Scholars Hub, 2026)
Between the Sahara Desert and the Sudanese Savannah, the Sahel region has become a contested geopolitical space. This study analyses how France is reconstructing its hegemony following its military withdrawal through the rhetoric of Emmanuel Macron (2021 and 2025). Using Critical Discourse Analysis (Fairclough, 1995) and the theory of spatial production (Lefebvre, 1974), this study examines how the discourses of “partnership” and “security” are employed to maintain French influence. Qualitative methods were applied to Macron's speeches, French media, and statements by former presidents of Sahel countries. The results show that France is redefining the Sahel as a ‘crisis zone’ requiring external management, through a shift in the military's role into the economic and symbolic spheres. Even with a diminished military footprint, France’s hegemony continues to be articulated through discourse. Thus, it demonstrates how discursive strategies uphold neocolonial power after physical disengagement. This study contributes to postcolonial and geopolitical studies by showing that hegemony can be maintained through discursive strategy, even after the decrease in physical presence.